A Global Framework for Carbon-Smart Agricultural Systems: Evaluating the Role of Regenerative Practices in Carbon Sequestration and Emissions Mitigation - Dian Diani T (CV. HEI PUBLISHING INDONESIA, 2024)
Global agriculture must meet growing food demands while reducing greenhouse gas (GHG) emissions. This study proposes a global framework to assess regenerative agricultural practices within climate-smart agriculture (CSA) systems, focusing on their potential for soil carbon sequestration and GHG mitigation. Secondary data were collected from scientific literature and public databases on key regenerative practices, including agroforestry, cover crops, legume rotations, livestock integration, non-chemical inputs, and no-till farming. A meta-analysis was conducted to estimate average impacts on carbon sequestration and emissions reduction, leading to the development of a flexible, globally applicable evaluation framework. Findings show that all regenerative practices enhance soil carbon levels compared to conventional methods, with agroforestry and combined legume/non-legume cover crops showing the highest potential, particularly in perennial systems. Integrated approaches yielded stronger results than individual practices due to synergistic effects. However, outcomes varied significantly depending on local soil and climate conditions. The study reinforces the role of regenerative agriculture in addressing climate change and ensuring food security while providing a practical tool for policymakers and practitioners. It recommends further long-term research and the use of digital technologies to refine and adapt the framework across diverse agricultural contexts.